Microstructure and properties of Ag-Ti bimetal cathode materials by vacuum diffusion bonding for gold hydrometallurgy. (October 2020) - Zou, Juntao; Gao, Lei; Li, Xiang; Xue, Zhenyu; Sun, Lixing; Liang, Shuhua
Graphical abstract: Abstract: Cathode plate affects the quality and cost of gold refining. Ag-Ti bimetal cathode materials were fabricated by vacuum hot-press diffusion bonding in this paper. Microstructure morphology and an analysis of the bimetal show that metallurgical interface has been successfully constructed between the Ag and Ti. The interfacial layer consisted of the intermetallic compound AgTi and the solid solution α-Ti. The hardness at the interface reaches a maximum of 467 HV at a bonding temperature of 890 °C. The bath voltage of the Ag-Ti cathode plate is only 2/3 of that of the Ti cathode plate when the thickness ratio of Ag and Ti is 8:1. The gold yield is increased by 10 %, approaching 80 %.